Calcified miliary brain metastases with mitochondrial inclusion bodies. Issue 1 (January 1993) - Yamazaki, T; Harigaya, Y; Noguchi, O; Okamoto, K; Hirai, S
Abstract : A patient with calcified miliary brain metastases from lung adenocarcinoma is reported. Electron microscopic study of the metastatic tumour cells showed membranous inclusion bodies in mitochondria.